Analysis the Fulfilment of Physical and Psychological Needs of Convicted Criminal From An Islamic Law Perspective - Safiuddin Safiuddin; Muhammad Akbar; Muhammad Syarif Hasyim (State Institute for Islamic Studies Palu, 2020)
This study discusses the implementation of conditional leave (CL) in fulfilling prisoners' physical and phsychological need of prisoners from Islamic law perspectives. This study used qualitative method with data collection techniques through observation, indepth-interviews and written material analysis. Data was analysed through data reduction, presentation, verification, and drawing conclusions. The results of the study show that obligatory livelihoods for husbands with prisoner status was fulfilled through the efforts made by inmates such as a business that is still moving and producing that can be used by the wife to meet needs. Less implemented, this is based on the still potential of prisoners to provide for their wives needs through the provision of relatives even though the fulfillment of the quality of living needs is not optimal. While the fulfillment of the psychological needs supported by inmates, namely giving love, education, and distribution of sexual desires, in the form of face-to-face and joking with his wife, while channeling sexual desires in the effort to fulfill the inner living is rarely done except for prisoners getting conditional leave (CL) ). The livelihood of the husband who is undergoing a period of punishment is not contrary to Islamic law, although on one hand the status remains as a family head who has obligations that must be fulfilled. Islam views this with three legal stipulations, the first is the obligation to make a living, the second is the obligation to earn a living and the third is the obligation to make a living fall.